Effects of screen filter on visibility of alphanumeric presentation on CRT and LCD monitors. - Zunjic, A; Ristic, L; Milanovic, D (2012)
In this paper, a research that deals with the problem of determining of the visibility of the alphanumeric presentation on CRT and LCD screens is presented, in conditions when the screen filters are used, and when they are not used. A methodology that can be used for determination of the visibility of alphanumeric symbols on VDT screens is presented. It is determined the existence of differences in visibility of alphanumeric presentations when screen filters are used, compared to conditions when they are not used. This difference was statistically significant, while the visibility of the presented alphanumeric symbols on CRT and LCD screens that use screen filters is lower than when they are not used. For this reason, the use of protective screen filter is recommended in circumstances where a very high level of glare exists, when the visual fatigue is common appearance and when a user performs a task that does not depend on the detection of stimuli whose RGB values are low.